Targeting NEK2 as a promising therapeutic approach for cancer treatment - Fang, Yanfen (Cell Cycle, 2016)
Never in Mitosis (NIMA) Related Kinase 2 (NEK2) plays a key role in regulating mitotic processes, including centrosome duplication and separation, microtubule stabilization, kinetochore attachment and spindle assembly checkpoint. NEK2 is aberrantly overexpressed in a wide variety of human cancers and has been implicated in various aspects of malignant transformation, including tumorigenesis, drug resistance and tumor progression. The close relationship between NEK2 and cancer has made it an attractive target for anticancer therapeutic development; however, the mechanisms of how NEK2 coordinates altered signaling to malignant transformation remains unclear. In this paper, we discuss the functional roles of NEK2 in cancer development; highlight some of the significant NEK2 signaling in cancer, and summarize recent advances in the development of NEK2 inhibitors.